PERAN SENTRAL BUNDA MARIA DALAM PROSESI ARAK-ARAKAN PATUNG TUAN MA DI LARANTUKA (SUATU UNGKAPAN KEARIFAN LOKAL DALAM TRADISI RELIGIUS) - R.F Bhanu Viktorahadi (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2020)
Saint Mary’s figure is so exclusive to the people of Larantuka City which appear in the Semana Santa ritual. In Lera Wulan Tanah Ekan’s Lamaholot ethnic pre-Catholic religious system which views female figures as representations of the universe, it brings forth an allegation that there is a correlation with the cultural dominance of the Virgin Mary figure. This paper analyzes Semana Santa’s, especially Tuan Ma procession phenomenon as the main indicator of Larantuka society’s exclusive appreciation and perception background toward the Virgin Mary and try to seek, Larantuka people as Lamaholot ethnic have a local wisdom called Lewotana covering all the values they embrace and implement, including the value in their religious system. The phenomenon of the cultural system religion of Larantuka society alteration from Lera Wulan Tanah Ekan and Lewotana into Catholic culture only occurs at the level of social behavior and artifacts, the idea of the value of the sacred women figure who is considered as a representation of the universe still exist in the cognitive nature of Larantuka society with the figure of the Virgin Mary as a substitution process media of feminist value along with symbol as ‘place’ meaning to the admiration and respect to woman figure, especially mother.Keyword: Tuan Ma, Semana Santa, Akulturasi, Kearifan Lokal, Feminisme.